The foraging potential of the Holocene Cape south coast of South Africa without the Palaeo-Agulhas Plain. (1st May 2020) - Wren, Colin D.; Botha, Susan; De Vynck, Jan; Janssen, Marco A.; Hill, Kim; Shook, Eric; Harris, Jacob A.; Wood, Brian M.; Venter, Jan; Cowling, Richard; Franklin, Janet; Fisher, Erich C.; et al.
Abstract: The Palaeo-Agulhas Plain formed an important habitat exploited by Pleistocene hunter-gatherer populations during periods of lower sea level. This productive, grassy habitat would have supported numerous large-bodied ungulates accessible to a population of skilled hunters with the right hunting technology. It also provided a potentially rich location for plant food collection, and along its shores a coastline that moved with the rise and fall of sea levels. The rich archaeological and paleontological records of Pleistocene sites along the modern Cape south coast of South Africa, which would have overlooked the Palaeo-Agulhas Plain during Pleistocene times of lower sea level, provides a paleoarchive of this extinct ecosystem. In this paper, we present a first order illustration of the " palaeoscape modeling " approach advocated by Marean et al. (2015). We use a resourcescape model created from modern studies of habitat productivity without the Palaeo-Agulhas Plain. This is equivalent to predominant Holocene conditions before recent landscape modifications for farming. We then run an agent-based model of the human foraging system to investigate several research questions. Our agent-based approach uses the theoretical framework of optimal foraging theory to model human foraging decisions designed to optimize the net caloric gains within a complex landscape of spatially and temporally variable resources. We find that during the high sea-levels of MIS 5e (+5–6 m asl) and the Holocene, the absence of the Plain left a relatively poor food base supporting a much smaller population relying heavily on edible plant resources from the current Cape flora. Despite high species diversity of plants with edible storage organs, and marine invertebrates, encounter rates with highly profitable resources were low. We demonstrate that without the Palaeo-Agulhas Plain, human populations must have been small and low-density, and exploited plant, mammal, and marine resources with relatively low caloric returns. The exposure and contraction of the Palaeo-Agulhas Plain was likely the single biggest driver of behavioural change during periods of climate change through the Pleistocene and into the transition to the Holocene. Highlights: Agent-based model of Later Stone Age human foraging in coastal South Africa. Reconstructed food resource landscape including mammals, shellfish, and plants. Sustainable population is under 20 individuals/100 km^2. Long foraging days (10 + hours per day) and small groups needed to survive. Edible plants, including USOs, make up 80% or more of the diet.